Environment Law and Natural Sustainability resources: case of Pawon Cave Area Conservation Gunung Masigit Village, Cipatat District, West Bandung - A Hadian Pratama Hamzah (Faculty of Law, Universitas Pekalongan, 2022)
This study aims to examine the sustainability of the conservation of the Pawon Cave area and the factors that influence it. Sustainable development includes ecology, the region's social and economic benefits, and mining potential. The method used is a mixture of qualitative and quantitative. Herein, the community access to the Pawon Cave area is gardening, taking firewood, and taking grass. Processing and minimization of soil erosion are well managed, including a terracing system. Plants and animals in the area are maintained with no logging or hunting. The site provides benefits such as water, rice, vegetables, and fruits, as well as fertilizer for agriculture. Moreover, factors that affect the sustainability of the conservation of the Pawon Cave area are policy support from the government and having adequate human resources to manage the place. The implementation of the policy has shown that it is appropriate to support conservation efforts such as prevention of mining, preservation of springs, and protection of plants and animals in the area. Several construction facilities have also been built to support tourism. The coaching and training program for the caretaker of the Pawon Cave area is an effort to keep the area manager's human resources professionals. The incentives given by the government to the Provincial Jupel are 500,000/month, and the Regency Jupel is 450,000/month.